The experience of home for social housing tenants with a disability: security and connection but limited control. Issue 1 (2nd January 2020) - Aplin, Tammy; Canagasuriam, Shari; Petersen, Maree; Gustafsson, Louise
ABSTRACT: Research exploring the meaning of home is well established; however, limited attention has been paid to contexts outside of western, owner-occupied homes. One context which requires further investigation is the experience of home for adults with disability living in social housing. This study aimed to investigate this experience in Australia. Fifteen households participated in in-depth interviews. Two themes "home is still home" and "loss of control" emerged from the thematic analysis. Participants described their homes' as providing security, stability and a sense of "home", but many also experienced limited control over the location, condition, and modification and maintenance of their home. The study highlights the importance of secure tenure, the need to support people with a disability during housing transitions, and the impact of policy on the experience of home. Ongoing research on the impact of housing policies on the lives of people with a disability will be key to improved policy.